Oncologist perspectives on tumor boards: Virtual meetings and EHR integration. Issue 28 (1st October 2022) - Arafat, Waddah; Fu, Paul; Wagner, Andrew J.; Osterman, Travis; Martin, Daniel; Sugalski, Jessica; Heinrichs, Tricia; Racz, Jennifer M.; Tevaarwerk, Amye Juliet
Abstract : 46 Background: Tumor boards (TBs) are considered a key component for ensuring high quality cancer care. However, little is known about TB operational aspects that impact effectiveness. We aimed to understand how TBs leverage Electronic Health Record (EHR) functionalities and how pandemic-driven transitions from in-person TBs to virtual TBs impacted TB quality and effectiveness. Methods: The National Comprehensive Cancer Network (NCCN) Oncology EHR Advisory Group formed a Workgroup to assess the current state of TBs, obtain providers' views on ideal TB state, and develop recommendations for improving TB quality and effectiveness. The Workgroup surveyed providers in various specialties at 31 NCCN Member Institutions in March 2022. Results: 846 providers from 27 institutions responded to the survey (n = 76 respondents were excluded from analysis because they reported not participating in TBs). Almost all (n = 764/767, 99%) indicated that one or more participants always or frequently attended TB meetings virtually. When comparing (newly established) virtual to (pre-pandemic) in-person TBs, 69% indicated increased attendance at virtual TBs. 65% reported no change in case volume, and 56% reported unchanged discussion quality while 19% reported increased discussion quality when comparing virtual to in-person TB meetings. In regards to EHR integration, several gaps between current and ideal state were noted. For instance, 40% always or frequently added patients to the TB roster via the EHR, but 57% reported this functionality to be very important or important for TBs. Additionally, 53% always or frequently document TB recommendations within the EHR, while 87% indicated EHR documentation of recommendations as very important or important. Respondents reported that barriers to documentation include resource constraints, concerns with patient access to documentation, legal and liability concerns, and poor EHR functionality. Conclusions: Overall, the majority of responding providers reported virtual TBs to be at least similar in quality to in-person TB meetings. A major gap identified by this study is the lack of documentation of TB recommendations in the EHR. Workflows and EHR functionalities could be improved to fully optimize the EHR for TB management and documentation.Comparison between current and ideal state for TBs. Domain (N = 767) Respondents Reporting Always or Frequently in Current State Respondents Indicating Very Important or Important in Ideal State One or more participants attend my tumor board virtually 99% 96% Tumor board recommendations are documented within the EHR 53% 87% Each patient discussion has a "tumor board" note or document in the EHR 46% 80% Tumor board patient lists are visible in the EHR prior to the meeting 35% 58% The addition of patients to the tumor board roster are submitted via the EHR 40% 57% Documentation for my tumor board occurs in real time within the EHR 31% 52%